Processing and properties of boron carbide (B4C) reinforced LDPE composites for radiation shielding - Avcioglu, Suna; Buldu, Merve; Kaya, Figen; Ustundag, Cem Bulent; Kam, Erol; Menceloglu, Yusuf Ziya; Kaptan, Hayri Yilmaz; Kaya, Cengiz (ELSEVIER SCI LTD, 2020)
In the present work, boron carbide (B4C) particles were synthesized with sol-gel technique following with heat treatment at 1500 degrees C in an argon atmosphere. 3-(Triethoxysilyl)-propylamine, a silane coupling agent, was doped on to the surface of synthesized B4C particles. The surface modified B4C particles were embedded in LDPE matrix in order to obtain flexible, lightweight and environmentally friendly shielding materials. The effect of surface functionalization and concentration of boron carbide on its distribution characteristics in the polymer matrix and its effects on the mechanical and neutron shielding properties of the composites are examined. The results showed that high purity-fully crystalline B4C powders with polyhedral-equiaxed morphology in the size range of 20 nm-500 nm were produced. It was found that even the very low amount (0.6-1.7 wt%) of incorporated nano/sub-micron B4C particles in LDPE matrix improved the neutron shielding (up to 39%), tensile strength (9.3%) and impact resistance (8%) of the composites.
Keywords: Sol-gel; Boron carbide; LDPE; Composite; Neutron shielding; Mechanical properties; SPECTROSCOPY; POWDER; NANOFIBERS; PLATFORM; GAMMA; Materials Science